Health and Economic Outcomes in the Alumni of the Wounded Warrior Project : 2010–2012 - Heather Krull, Mustafa Oguz (RAND Corporation, 2014)
Since 2003, the not-for-profit Wounded Warrior Project (WWP) has sought to offer support for and raise public awareness of those injured during service on or after September 11, 2001. To this end, WWP gives members, or alumni, access to programs that nurture mind and body, as well as facilitate economic well-being. Central to WWPâ€™s success are its assessment efforts. In 2009, RAND researchers helped WWP design a web-based survey that would help the organization evaluate how well it is meeting its three primary strategic goals: ô€´ô€€ Ensure that wounded warriors are well-adjusted in mind and spirit. ô€´ô€€ Ensure that wounded warriors are well-adjusted in body. ô€´ô€€ Ensure that wounded warriors are economically empowered. The survey, designed by RAND researchers, was administered in 2010, 2011, and 2012 by the statistical research firm Westat. The firm also prepared initial interpretive reports for WWP. WWP asked RAND to utilize the survey results to provide more-detailed analysis. Specifically, WWP was interested in the way individuals from different subgroups, as defined by demographic and service characteristics, were meeting the strategic goals. WWP also wished to gain a wider view of its organizational performance by understanding how alumnus outcomes compared with the outcomes of other veteran and nonveteran U.S. populations.